Introduction to probability: statistics and random processes - Pishro-Nik, Hossein ([Blue Bell, PA] : Kappa Research, LLC, 2014)
The book covers basic concepts such as random experiments, probability axioms, conditional probability, and counting methods, single and multiple random variables (discrete, continuous, and mixed), as well as moment-generating functions, characteristic functions, random vectors, and inequalities; limit theorems and convergence; introduction to Bayesian and classical statistics; random processes including processing of random signals, Poisson processes, discrete-time and continuous-time Markov chains, and Brownian motion; simulation using MATLAB and R.
Basic concepts -- combinatorics: counting methods -- discrete random variables -- continuous and mixed random variables -- joint distributions: two random variables.
Includes bibliographical references (pages 731-732) and index.
Keywords: PROBABILITIES; STATISTICS; STOCHASTIC PROCESSES